ANALISIS KOMPARATIF KINERJA KEUANGAN PERUSAHAAN SEBELUM DAN SESUDAH INITIAL PUBLIC OFFERING (IPO) DI BURSA EFEK INDONESIA (BEI) TAHUN 2016 - Unun Khoirun Nisak; Budiono Budiono (Media Mahardhika, 2020)
This study aims to analyze differences in the company's financial performance before and after the Initial Public Offering (IPO) on the Indonesia Stock Exchange in 2016. The observation period was conducted for 2 years before and 2 years after the IPO. The sampling technique was purposive sampling in order to get 12 companies. Variables used to measure financial performance are Current Ratio (CR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Return On Asset (ROA), Return On Equity (ROE), Total Asset Turn Over (TATO) ), and Fixed Asset Turn Over (FATO). This research uses a quantitative approach with statistical methods. The data analysis technique used is one sample Kolmogorof Smirnof to test the normality of the data and paired sample t-test and Wilcoxon signed rank test to test the hypothesis. The results of this study indicate that there are differences in the company's financial performance measured by CR, DAR, DER, and TATO before and after the Initial Public Offering (IPO) and there is no difference in the company's financial performance measured by ROA, ROE, and FATO before and after the Initial Public Offering (IPO). ). The results of overall financial performance after the IPO action have not been fully realized so that the company's expectations for creating better financial performance have not been realized.